Temperature dependence of the rate constant and product channels for the BrO + ClO reaction - Hills, AJ; Cicerone, RJ; Calvert, JG; Birks, JW (eScholarship, University of California, 1988)
We have measured the rate constant for the reactions BrO + ClO → Br + OClO (6a), BrO + ClO → Br + Cl + O2 (6b), and BrO + ClO → BrCl + O2 (6c) over the temperature range 241-408 K and found k6 = (8.2 ± 1.0) × 10-12 cm3 molecule-1 s independent of temperature. Measurement of the individual product branching ratios yielded values for channels 6a, 6b, and 6c equal to 0.55 ± 0.10, 0.45 ± 0.10, and < 0.02, respectively. Measurements of ozone in the stratosphere over Antarctica have shown that the springtime ozone column has fallen 40% from 1960 to 1985. The reaction above could account for a large fraction of the springtime "ozone hole" reported recently, provided that at least 20 ppt of total inorganic bromine is present, and it may provide a source of chlorine dioxide of sufficient magnitude to explain the recent measurements of this species in the Antarctic stratosphere. © 1988 American Chemical Society.